2018
DOI: 10.4193/rhin17.139
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab treats chronic rhinosinusitis with nasal polyps and asthma together-a real life study

Abstract: Omalizumab treatment for severe allergic asthma also improves co-existent CRSwNP. Further clinical studies of current and emerging biological agents for severe asthma should include upper airway outcomes. These agents may be effective for severe CRSwNP and comparative studies with surgery are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 16 publications
4
62
0
6
Order By: Relevance
“…To date, one study evaluated omalizumab vs sinus surgery in patients with grade 3 CRSwNP and asthma. 49 It was concluded that omalizumab is equally effective in reducing SNOT-22 at 16 weeks to sinus surgery. However, large-scale studies are needed to confirm these findings in order to decide upon whether or not biologics could be a valid alternative to primary sinus surgery.…”
Section: Indic Ations For B Iolog Ic Smentioning
confidence: 99%
See 1 more Smart Citation
“…To date, one study evaluated omalizumab vs sinus surgery in patients with grade 3 CRSwNP and asthma. 49 It was concluded that omalizumab is equally effective in reducing SNOT-22 at 16 weeks to sinus surgery. However, large-scale studies are needed to confirm these findings in order to decide upon whether or not biologics could be a valid alternative to primary sinus surgery.…”
Section: Indic Ations For B Iolog Ic Smentioning
confidence: 99%
“…36,[42][43][44][45][46] A number of trials have been done with biological therapies for CRSwNP. [47][48][49][50] As these drugs enter the market, it necessitates the medical community to reflect on the positioning of these therapies in the current care pathways of the upper and lower airways. 51,52 The European Forum for Research and Education in Allergy…”
Section: Introductionmentioning
confidence: 99%
“…105,106 High numbers of MCs have been described in NPs, and MCs were implicated in shaping a type 2 inflammatory milieu. 107 Anti-IgE was effective in reducing nasal symptoms and NP size in patients with CRS without or with NPs and eosinophilic inflammation, [108][109][110] which is in line with a possible contribution of MCs.…”
Section: Atopic Diseasesmentioning
confidence: 58%
“…In the last years a number of studies has appeared that show effectiveness of anti-IgE (Omalizumab) (4)(5)(6) , anti-IL-5 (Mepolizumab) (7) and antiIL4Ra (Dupilumab) (8) .…”
mentioning
confidence: 99%